2019
DOI: 10.1016/j.jaci.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of the ectopic olfactory receptor OR10G7 in patients with atopic dermatitis

Abstract: Background: Ectopic olfactory receptors (ORs) are found in the skin, but their expression and biological function in normal skin and skin form patients with atopic dermatitis (AD) are unknown. Objectives: We sought to characterize the expression of ORs in the skin and assess OR-mediated biological responses of primary human keratinocytes in the presence of odorant ligands. Methods: OR expression was examined by using wholetranscriptome sequencing of skin tape strips collected from patients with AD and healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…Although the precise mechanisms are not well defined, ORs represent promising therapeutic targets. Ligands for ORs such as OR51E1, OR10G7, and OR1D2, which were included in this study, are candidate treatments for conditions ranging from prostate cancer and chronic obstructive pulmonary disease (COPD) to atopic dermatitis ( Kalbe et al., 2016 ; Maβberg et al., 2016 ; Tham et al., 2019 ). We therefore anticipate that the predictions and the analysis of known and candidate OR ligands from this study will also have value in non-olfactory studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise mechanisms are not well defined, ORs represent promising therapeutic targets. Ligands for ORs such as OR51E1, OR10G7, and OR1D2, which were included in this study, are candidate treatments for conditions ranging from prostate cancer and chronic obstructive pulmonary disease (COPD) to atopic dermatitis ( Kalbe et al., 2016 ; Maβberg et al., 2016 ; Tham et al., 2019 ). We therefore anticipate that the predictions and the analysis of known and candidate OR ligands from this study will also have value in non-olfactory studies.…”
Section: Discussionmentioning
confidence: 99%
“…Increased mRNA levels of OR10G7 were recently detected by skin tape stripping in atopic dermatitis patients in the upper epidermal layers. Although this may constitute a potential mechanism of odorant-induced skin inflammation in AD patients [106,107], an earlier study found olfactory receptor genes to be downregulated in AD [40]. This may reflect the above-mentioned difficulties in inter-study comparison or may argue for the high diversity seen in the AD pathophysiology.…”
Section: Atopic Dermatitismentioning
confidence: 92%
“…The OR superfamily has approximately 400 functional members in humans. Although virtually all ORs are expressed in the olfactory epithelium, the OR genes expressed in ectopic tissues are tissue- and condition-specific [ 23 , 34 , 35 , 36 ]. In this study, we confirmed that the expression of at least 12 ORs was significantly upregulated in UV-irradiated or inflamed keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that TNF-α/IFN-γ treatment and UVB irradiation upregulated several OR genes in keratinocytes. These increases may be functionally interpreted in two different ways: (i) OR receptors act as mediators of the events that initiate specific pathological conditions [ 23 ], and (ii) these receptors have protective functions and their expression is increased to compensate for unfavorable conditions [ 22 , 34 ]. To differentiate between two possible explanations for increased OR expression, we used a known, specific ligand to each receptor and investigated the receptor-mediated effects on the barrier function-related gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation